Health-related quality of life in paediatric patients with intoxication-type inborn errors of metabolism: analysis of an international data set - Bösch, Florin; Landolt, Markus A.; Baumgartner, Matthias R.; Zeltner, Nina; Kölker, Stefan; Gleich, Florian; Burlina, Alberto; Cazzorla, Chiara; Packman, Wendy; Schwartz, Ida V. D.; Vieira Neto, Eduardo; Ribeiro, Márcia G.; et al. (Journal of inherited metabolic disease, 2021)
Acute intoxication-type inborn errors of metabolism (IT-IEM) such as urea cycle disorders and non-acute IT-IEM such as phenylketonuria have a major impact on paediatric patients' life. Patients have to adhere to a strict diet but may face neurocognitive impairment and - in acute diseases - metabolic decompensations nevertheless. Research on the subjective burden of IT-IEM remains sparse. Studies with appropriate sample sizes are needed to make valid statements about health-related quality of life (HrQoL) in children and adolescents with IT-IEM. Six international metabolic centres contributed self-reports and proxy reports of HrQoL (assessed with the Paediatric Quality of Life Inventory) to the final data set (n = 251 patients; age range 2.3-18.8 years). To compare HrQoL of the patient sample with norm data and between acute and non-acute IT-IEM, t tests were conducted. To examine the influence of child age, sex, diagnosis and current dietary treatment on HrQoL, multiple linear regression analyses were conducted. Self-reports and proxy reporst showed significantly lower HrQoL total scores for children with IT-IEM compared to healthy children. Current dietary treatment significantly predicted lower proxy reported total HrQoL. Children with non-acute IT-IEM reported significantly lower psychosocial health and emotional functioning than children with acute IT-IEM. The patient sample showed significantly impaired HrQoL and a diet regimen remains a risk factor for lower HrQoL. Differences in HrQoL between acute and non-acute IT-IEM subgroups indicate that factors beyond symptom severity determine the perception of disease burden. Identifying these factors is of crucial importance to develop and implement appropriate interventions for those in need.
Zuerst publiziert: 12. August 2020
Gesehen am 09.09.2025